2021
DOI: 10.1016/j.clnu.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of bioelectrical impedance analysis for body composition assessment in children with obesity aged 8-14y

Abstract: Background & aims: The aim was to generate a predictive equation to assess body composition (BC) in children with obesity using bioimpedance (BIA), and avoid bias produced by different density levels of fat free mass (FFM) in this population. Methods: This was a cross-sectional validation study using baseline data from a randomized intervention trial to treat childhood obesity. Participants were 8 to 14y (n ¼ 315), underwent assessments on anthropometry and BC through Air Displacement Plethysmography (ADP), Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The multivariate regression analysis did not show an association between BMI and 90-day mortality, but rather between PhA and mortality in our study. Some studies showed that BIA measurements are better than anthropometry and blood biochemical analysis in the nutritional assessment of patients ( 4 , 13 15 ). These findings emphasize the importance of body composition analysis to anthropometry in the ability of the nutrition assessment and predicting clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate regression analysis did not show an association between BMI and 90-day mortality, but rather between PhA and mortality in our study. Some studies showed that BIA measurements are better than anthropometry and blood biochemical analysis in the nutritional assessment of patients ( 4 , 13 15 ). These findings emphasize the importance of body composition analysis to anthropometry in the ability of the nutrition assessment and predicting clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Body density was calculated by ADP (Bod-Pod ® , COSMED, Albano Laziale, Italy). Data for calculation of body fat by this plethysmographic technique has been published to agree closely with the classic gold standard underwater weighing (hydrodensitometry) in children [ 20 , 22 ] and has been used as the reference method to validate other body composition measurements in children [ 23 ]. The Siri equation was used to calculate BF% from body density.…”
Section: Methodsmentioning
confidence: 99%
“…A bio-impedance analyzer (BIA) (Medigate Company Inc., Dan-dong Gunpo, Korea) was used to assess fat mass and muscle mass. There is acceptable validity (>0.85) and correlation (r=0.73-0.96) of BIA results with reference methods such as underwater weighing, Air displacement plethysmography (ADP), and dual-energy x-ray absorptiometry (DXA) that has been validated in healthy persons (39), athletes (40), patients (41) and obese children (42).…”
Section: Anthropometry Body Composition and Cardio-respiratory Fitnessmentioning
confidence: 99%